Digitalisation- its Impact on Customer Buying Behviour (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Digitalisation has transformed the way retail operates, influencing both the behaviour ofconsumers and the operations of retailers. With the widespread adoption of e-commerce andmobile technology, a consumer has come to expect a seamless shopping experience thatcombines online and offline channels. Retailers, in turn, have responded by adopting newtechnologies such as personalized marketing, automated inventory management, AR, VR, AI,product customization, robotics, shelf restocking, QR code, cashier less stores etc.